Novel insights into palatal shelf elevation dynamics in normal mouse embryos - Goering, Jeremy P.; Moedritzer, Michael; Stetsiv, Marta; Isai, Dona Greta; Hufft-Martinez, Brittany M.; Tran, An J.; Umar, Zaid; Rickabaugh, Madison K.; Keselman, Paul; Chauhan, Munish; Tran, Pamela V.; Brooks, William M.; et al. (Frontiers in Cell and Developmental Biology, 2025)
Development of the embryonic palate requires that the palatal shelves (PS), which extend from maxillary processes, to grow bilaterally and vertically alongside the tongue. This growth continues until embryonic day (E) 13.5, after which the PS elevate above the tongue and adhere, completing the process by E14.5. Current models indicate that this elevation process involves a complex vertical-to-horizontal PS reorientation. While earlier studies have implied that reorientation occurs rapidly, the precise timing has not been resolved. Time-restricted pregnancies with a 1-h resolution showed that in 97% of C57BL/6J embryos, the PS were unelevated at E14.0. However, 6 h later, at E14.25, the PS had completed elevation in 80% of embryos, indicating that the PS elevate in a rapid and constrained timeframe. Interestingly, all E14.25 embryos with unelevated PS (20%) were female, suggesting sex differences in C57BL/6J PS elevation. In FVB/NJ embryos, the elevation window started earlier (E13.875-E14.25), and without any sex differences. An intermediate stage with unilateral PS elevation was frequently observed. Magnetic resonance imaging (MRI) of various stages showed that PS elevation began with posterior bilateral bulges, which then progressed laterally and anteriorly over time. During elevation, we observed increased cell proliferation in the PS lingual region. Within the bulge, cell orientation was tilted towards the tongue, and actomyosin activity was increased, which together may participate in horizontal projection of the bulge. Thus, our data reveal novel insights into rapid dynamic changes during PS elevation, and lay the foundation for future studies of normal and abnormal palatogenesis.